2017
DOI: 10.1177/0883073817726681
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Brain Magnetic Resonance Imaging in Neonatal Hypoxic-Ischemic Encephalopathy: A Meta-analysis

Abstract: Neonatal brain MRI provides prognostic information on outcome beyond early infancy in hypoxic-ischemic encephalopathy and therapeutic hypothermia does not change its prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 35 publications
1
29
0
5
Order By: Relevance
“…In the era of predates hypothermia treatment, late MRI (8-30 days) had higher sensitivity but lower specificity than early MRI (1-7 days) (36). However, the current literature does not provide detailed individual data on the time of neonatal brain MRI in HT (37). In the present review, late MRI predicted an unfavorable neurological outcome with a sensitivity and specificity of 0.88 and 0.88, respectively, whereas early MRI showed less specificity of 0.73.…”
Section: Discussionmentioning
confidence: 96%
“…In the era of predates hypothermia treatment, late MRI (8-30 days) had higher sensitivity but lower specificity than early MRI (1-7 days) (36). However, the current literature does not provide detailed individual data on the time of neonatal brain MRI in HT (37). In the present review, late MRI predicted an unfavorable neurological outcome with a sensitivity and specificity of 0.88 and 0.88, respectively, whereas early MRI showed less specificity of 0.73.…”
Section: Discussionmentioning
confidence: 96%
“…[109][110][111] Importantly, the prognostic value of brain MRI is not affected by therapeutic hypothermia. 109,110,112 A meta-analysis including 860 infants with HIE reported that brain MRI in the neonatal period has a sensitivity of 91% (95% confidence interval [CI]: 87-94%) and specificity of 51% (95% CI: 45-58%) for predicting adverse neurodevelopmental outcomes at !1 year. 113 Interestingly, deep gray matter lactate/NAA peak-area ratio, as assessed on MR spectroscopy, was the most accurate quantitative MRI biomarker for predicting neurodevelopmental outcomes after HIE.…”
Section: Neuroimaging Predictors Magnetic Resonance Imagingmentioning
confidence: 99%
“…Морфологические показатели ЦНС, полученные с применением НСГ или магнитно-резонансной томографии (МРТ), коррелируют с частотой развития моторных или психических нарушений, а также эпилепсии у детей [22]. Ограничения МРТ делают этот метод обследования недоступным для рутинного использования в широкой клинической практике, поэтому методом «прикроватной» оценки морфологии ЦНС остается НСГ [23].…”
Section: таблица 8 прогностическая ценность цикличности сон-бодрствоunclassified
“…Поздние атрофические изменения головного мозга представлены атрофией подкорковых ядер, лейкомаляцией или энцефаломаляцией, которые сопровождаются вентрикулодилятацией и/или расширением наружных ликворных пространств и ассоциированы с тяжелым неврологическим исходом заболевания [22]. Преобладание атрофических процессов в обследуемой группе на момент выписки совпадает с данными исследований, описывающих ассоциацию патологических паттернов аЭЭГ и морфологического исхода заболевания [24].…”
Section: таблица 8 прогностическая ценность цикличности сон-бодрствоunclassified